2017
DOI: 10.1136/rmdopen-2017-000458
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is a strong predictor of worse clinical outcomes and treatment responses in early rheumatoid arthritis: results from the SWEFOT trial

Abstract: ObjectivesThe aim of this paper was to analyse the impact of obesity, in addition to known predictors, on disease outcome in early rheumatoid arthritis (RA).MethodsBody mass index (BMI) was available in 260 patients from the Swedish pharmacotherapy trial (SWEFOT). Differences in disease activity (DAS28), functional impairment (HAQ), pain (Visual Analogue Scale, VAS-pain) and radiographic damage were evaluated over 24 months between BMI categories (obese BMI >30, n=43; overweight BMI=25–29.9, n=74; normal BMI <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 28 publications
9
55
1
Order By: Relevance
“…(67) IL-6 inhibitors, comprising the relatively new agent tocilizumab, inhibit IL-6mediated signalling and induce B-regulatory cells, decreasing pro-inflammatory cytokines. (68) We found that the studies involving TNF-α inhibitors were associated with different outcomes: four studies (2,10,16,17) were associated with positive outcomes, three studies (25,26,29) with neutral outcomes and ten studies (11,(32)(33)(34)40,55,56,61,62,65) with negative outcomes. Rituximab was associated with positive, (17) neutral (23) and negative (11,56) outcomes, while tocilizumab was similarly associated with positive, (15) neutral (22,27) and negative (11,56) outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…(67) IL-6 inhibitors, comprising the relatively new agent tocilizumab, inhibit IL-6mediated signalling and induce B-regulatory cells, decreasing pro-inflammatory cytokines. (68) We found that the studies involving TNF-α inhibitors were associated with different outcomes: four studies (2,10,16,17) were associated with positive outcomes, three studies (25,26,29) with neutral outcomes and ten studies (11,(32)(33)(34)40,55,56,61,62,65) with negative outcomes. Rituximab was associated with positive, (17) neutral (23) and negative (11,56) outcomes, while tocilizumab was similarly associated with positive, (15) neutral (22,27) and negative (11,56) outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Body mass index, a modifiable and easily recognized factor, has been reported to be associated with clinical response to IFX among RA patients in several studies. [6][7][8][9][10] A clinically important question is whether BMI at treatment initiation also influences treatment response to other bDMARDs other than IFX, thus we conducted this study to determine the relationship between baseline BMI and clinical response to TCZ among RA patients using our prospective cohort study data. Although multiple clinical response criteria and different comparison methods (quantitative and qualitative comparison) have been utilized, non-significant evidence was found and our results are in accordance with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…6 Subsequently, several studies have replicated the negative association of BMI at initial treatment with clinical response to IFX, RA patients with higher BMI having decreased likelihood to achieve favorable clinical response. [7][8][9][10] Intriguingly, one study performed by Gremese et al 7 consisting of 641 patients with longstanding RA patients treated by three types of TNF-a inhibitors (adalimumab, etanercept, and IFX) found that obese patients were less likely to achieve remission compared with non-obese patients when all these three types of TNF-a inhibitors were considered. When data were analyzed according to the type of TNF-a inhibitor separately, significant evidence was only found for IFX, and the results indicated that obesity was particularly associated with clinical response to IFX.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations